Hormonas AIA, ANA, AG3 para estimular la germinación de semilla de palma aceitera (Elaeis guineensis) - Jimenez Carpio, Martin Alfredo (2015)
The research was conducted in the Quinindé canton in the province of Esmeraldas, whose geographical location: 00 ° 13'33 "north latitude and 73 ° 26'00" west longitude at an altitude of 115 meters above sea level, aiming at improving the system germination seed oil palm (Elaeis guineensis) through the use of growth regulators, using a completely randomized design factorial arrangement with three for three with 9 treatments, three replicates and eight observations per experimental unit, with the variable days of germination, germination percentage and vigor distributed in the following treatments: T1 A1 naphthaleneacetic acid (NAA) + B1 125 Lˉ¹, T2 A1 naphthaleneacetic acid (NAA) + B2 250 mg Lˉ¹, T3 A1 naphthaleneacetic acid (NAA) + B3 500 Lˉ¹ mg, T4 A2 indoleacetic acid (IAA) + B1 125 mg Lˉ¹ T5 A2 indoleacetic acid (IAA) + B2 250 mg Lˉ¹ T6 A2 indoleacetic acid (IAA) + B3 500 mg Lˉ¹, T7 A3 gibberellic acid (GA3) + B1 125 Lˉ¹ mg, T8 A3 gibberellic acid (GA3) + B1 250 mg Lˉ¹ and T9 A3 gibberellic acid (GA3) + B1 500 mg Lˉ¹. The results in the variable germination showed no statistical difference which which average ranging from 7.33 to 14 days, the germination percentage was obtained average were obtained ranging from 59.72 to 79.16% and there is a statistically equal in all treatments and the force moving average ranging from 46.68 to 88.67% with no statistical difference according to Tukey test at 0.05% were obtained. It is concluded that the use of growth regulators with different concentrations treatment T9 (A3 gibberellic acid (GA3) + B1 500 mg BAP Lˉ¹ positively influenced the three variables studied in the seed oil palm (Elaeis guineensis).